Effects of HSV-G47∆ oncolytic virus on telomerase and telomere length alterations in glioblastoma multiforme cancer stem cells under hypoxia and normoxia conditions - Vazifehmand, Reza; Saeed Ali, Dhuha; Monem Homaie, Foroozandeh; Molaei Jalalvand, Fatemeh; Othman, Zulkefley; Deming, Chau; Stanslas, Johnson; Sekawi, Zamberi (Bentham Science Publishers, 2024)
Background: Due to the existence of tumor stem cells with tumorigenicity properties and resistance patterns, treatment of glioblastoma is not easy. Hypoxia is a major concern in glioblastoma therapy. Telomerase activity and telomere length alterations have been known to play a critical role in glioblastoma progression and invasion. Objective: This study aimed to investigate the effects of HSV-G47∆ oncolytic virus on telomerase and telomere length alterations in U251GBMCSCs (U251-Glioblastoma cancer stem cells) under hypoxia and normoxia conditions. Methods: U251-CSCs were exposed to the HSV-G47∆ virus in optimized MOI (Multiplicity of in-fection=1/14 hours). An absolute telomere length and gene expression of telomerase subunits were determined using an absolute human telomere length quantification PCR assay. Furthermore, a bioinformatics pathway analysis was carried out to evaluate physical and genetic interactions between dysregulated genes with other potential genes and pathways. Results: Data revealed that U251CSCs had longer telomeres when exposed to HSV-G47Δ in nor-moxic conditions but had significantly shorter telomeres in hypoxic conditions. Furthermore, hTERC, DKC1, and TEP1 genes were significantly dysregulated in hypoxic and normoxic mi-croenvironments. The analysis revealed that the expression of TERF2 was significantly reduced in both microenvironments, and two critical genes from the MRN complex, MER11 and RAD50, were significantly upregulated in normoxic conditions. RAD50 showed a significant downregula-tion pattern in the hypoxic niche. Our results suggested that repair complex in the telomeric structure could be targeted by HSV-G47∆ in both microenvironments. Conclusion: In the glioblastoma treatment strategy, telomerase and telomere complex could be potential targets for HSV-G47∆ in both microenvironments.